2020
DOI: 10.1007/s11920-020-01212-w
|View full text |Cite
|
Sign up to set email alerts
|

Alliance Ruptures and Resolutions in Personality Disorders

Abstract: Purpose of Review This review provides an overview of the state of research on alliance ruptures and resolutions in the treatment of personality disorders (PDs). We discuss frequently used instruments to measure alliance ruptures and resolutions. We discuss the effectiveness of rupture resolution processes and highlight possible avenues for research to explore. Innovative assessments with the potential to reveal the link of ruptures and resolutions and mechanisms of psychotherapeutic change are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
8
0
5
Order By: Relevance
“…As a sidenote, and to put previous findings in this sample into perspective, in a previous study on silence in psychotherapy, we showed that in the present sample, silence can be problematic for the psychotherapeutic process ( Zimmermann et al, 2020 ). A further study based on the same data showed that there is an increased risk of withdrawal ruptures ( Schenk et al, 2019 , 2020 ) during psychotherapy in youth with BPD. We believe that these phenomena (silence and ruptures) are part of the normal psychotherapeutic process but that they imply a risk of being detrimental to the psychotherapeutic process because they can rigidify the interaction and hinder synchronization of the dyad in a larger sense.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As a sidenote, and to put previous findings in this sample into perspective, in a previous study on silence in psychotherapy, we showed that in the present sample, silence can be problematic for the psychotherapeutic process ( Zimmermann et al, 2020 ). A further study based on the same data showed that there is an increased risk of withdrawal ruptures ( Schenk et al, 2019 , 2020 ) during psychotherapy in youth with BPD. We believe that these phenomena (silence and ruptures) are part of the normal psychotherapeutic process but that they imply a risk of being detrimental to the psychotherapeutic process because they can rigidify the interaction and hinder synchronization of the dyad in a larger sense.…”
Section: Discussionmentioning
confidence: 85%
“…There are several psychotherapeutic approaches specifically developed for adolescent with BPD: e.g., dialectical behavior therapy for adolescents (DBT-A; Fleischhaker et al, 2011 ), mentalization-based treatment for adolescents (MBT-A; Rossouw and Fonagy, 2012 ), adolescent identity treatment (AIT; Foelsch et al, 2014 ), and schema-focused psychotherapy for adolescents ( Loose, 2015 ). The therapeutic process with BPD patients is often challenging because symptoms of BPD (e.g., rejection sensitivity) can hinder the construction of a good therapeutic relationship ( McMain et al, 2015 ) through an increased risk of ruptures of the therapeutic alliance ( Schenk et al, 2019 , 2020 ). Psychotherapy process research investigates active ingredients of therapeutic interventions and helps improve therapeutic approaches, as well as informing psychotherapists about the mechanisms of change and how they may leverage these actions ( Hardy and Llewelyn, 2015 ; Zimmermann et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging work investigating COVID-19 related worry (i.e., worry that is rooted in the uncertainty that surrounds the trajectory and consequences of COVID-19) has shown that worry about the pandemic is associated with poorer mental health (Kleinberg et al, 2020 ; Wang et al, 2020 ) and greater substance use (Rogers et al, 2020 ). Additionally, worry during the pandemic is related to higher anxiety, anxiety sensitivity, and depression (Baiano et al, 2020 ), and COVID-19 stress syndrome is conceptualized, in part, on the basis of the tendency to worry about pandemic-related factors (Taylor, 2020 ). Certain demographic factors (e.g., sex; Van der Vegt & Kleinberg, 2020 ) have been shown to influence the degree of experienced worry, but no work has evaluated the relation between individual differences in COVID-19 related worry and other emotional vulnerability factors that contribute to worse psychological outcomes among young adults.…”
Section: Introductionmentioning
confidence: 99%
“…As demographic data demonstrate, the sample carries a high burden of distress and impairment of personality functioningcomparable to other descriptions of poorly functioning patients with PD [43]. Such burden represents considerable clinical and personal vulnerability [44] effecting treatment processes [45][46][47] and treatment ruptures [12]. As one of few PD specific studies, the present investigation addresses the extraordinary situation of treatment interruption inflicted by the global Covid-19 pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…Emotional and relational difficulties like the capacity to trust and connect to other people, may impede regular treatment attendance and a stable treatment alliance [6][7][8][9][10]. In long-term therapies and treatments for PD, the alliance and management of alliance ruptures in early phases of treatment impact adherence and outcomes [11,12]. Studies of adolescents and young adults with PD have in particular, demonstrated considerable attachment insecurity [13,14].…”
Section: Introductionmentioning
confidence: 99%